Monitoring Variasi Spasial dan Temporal Genangan Danau Limboto Selama 2000-2015 Menggunakan Citra Modis dan Google Earth Engine - Lahay, Rakhmat Jaya (Universitas Negeri Gorontalo, 2022)
Changes in the Limboto Lake area can be monitored using remote sensing technology. Satellite imagery provides data regarding the surface area of the lake over a long period of time. However, conventional methods require large resources to process and analyze large remote sensing image data. This study utilizes geospatial information technology with the support of cloud computing to overcome these obstacles. The purpose of this study is to determine the inundation area of Lake Limboto from 2000 to 2015 and to analyze the trend of changes in inundation area over a 16 years period. The experimental results show a map of spatial and temporal changes in the inundation of Lake Limboto over 16 years. The trend of changes in the inundation area of Lake Limboto shows a decrease of 56.56 Ha every year. Further research needs to involve other factors such as rainfall and vegetation cover to see the effect of the inundation area of Lake Limboto.